, Стерильное одиночество” голубого цвета в рассказах Евгения Харитонова - Świetlik, Anna (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2018)
The main goal of this article was to examine the role of loneliness in the short stories by Yevgeny Kharitonov, whose pieces are considered to be representative for Russian gay literature (LGBT Literature) of the Soviet period. This article explores the reasons why loneliness and its subsequent stages became the main motif of Kharitonov's literary work. The term "sterile loneliness", brought to light by Eduard Limonov, perfectly reflects the deep sense of loneliness which is the worst struggle in the main character’s life. The author of this article attempts to show the psychological figure of a lonely and love-awaiting character in the short stories by Yevgeny Kharitonov.